1970
DOI: 10.1104/pp.45.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Promotion and Inhibition of Iron Accumulation in Soybean Plants

Abstract: Plants of four soybean (Glycine max L. Merrill) genotypes differing in their ability to accumulate iron were studied. The efficient genotypes were Hawkeye (HA) and A62-9 (E-9), and the inefficient ones were PI-54619-5-1 (PI) and A62-10 (1-10). When plants of opposite efficiency were grown in the same solution, iron accumulation decreased in the primary leaves of efficient plants, but it was unaffected or slightly reduced in the leaves of inefficient plants.Absorption of iron during a 24-hour period by 17-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Interest also attaches to the results of Engstrom and Howard (1970) who, in experiments carried out under non-sterile conditions, showed that the absorption of iron by soybean plants deficient in that element, was stimulated by transferring them to culture solution in which iron sufficient plants had previously been grown. None the less, the present results appear to conflict with those of Bromfield (1958) who grew oats under sterile and non-sterile conditions enclosed in boiling tubes with manganese supplied as the sulphate, a microbiologically produced oxide or a chemically prepared yMNOj.…”
Section: Discussionmentioning
confidence: 99%
“…Interest also attaches to the results of Engstrom and Howard (1970) who, in experiments carried out under non-sterile conditions, showed that the absorption of iron by soybean plants deficient in that element, was stimulated by transferring them to culture solution in which iron sufficient plants had previously been grown. None the less, the present results appear to conflict with those of Bromfield (1958) who grew oats under sterile and non-sterile conditions enclosed in boiling tubes with manganese supplied as the sulphate, a microbiologically produced oxide or a chemically prepared yMNOj.…”
Section: Discussionmentioning
confidence: 99%